2023
DOI: 10.1111/hiv.13489
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dolutegravir/rilpivirine in real‐world clinical practice. GeSIDA study 1119

Abstract: Introduction Dolutegravir/rilpivirine (DTG/RPV) is an effective antiretroviral (ART) regimen endorsed by clinical trials as a switch therapy. The aim of our study was to analyse the efficacy and safety of DTG/RPV in real‐world clinical practice. Methods Observational, multicentre study of patients who started DTG/RPV. Efficacy, adverse events and metabolic changes at 48 weeks were analysed. Results A total of 348 patients were included; median time of HIV infection was 21.1 years, 33.7% were AIDS cases; median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…suppression (94.2% in an on-treatment analysis) in a cohort more similar to ours [17]. Other studies based on clinical practice have reported similar results [18][19][20]; however, most of these studies do not separate results regarding sex.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…suppression (94.2% in an on-treatment analysis) in a cohort more similar to ours [17]. Other studies based on clinical practice have reported similar results [18][19][20]; however, most of these studies do not separate results regarding sex.…”
Section: Discussionsupporting
confidence: 81%
“…Resistanceassociated mutation (RAM) selection is uncommon in DTG + RPV failure, but RAMs in non-nucleoside reverse transcriptase inhibitor (E138K/A, K101E, L100I) and integrase strand transfer inhibitor (N155H) genes have been described in both clinical trials and real-worldpopulations [19,22]. In conclusion, our data and those of others [12,14,17,19,23] confirm that DTG + RPV as a switch strategy provides security in terms of virological failure and RAM selection.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation